Development of Multiple Array Vertical Wind Turbine - Azahar, Muhammad A’fif Mursyidi (Universiti Teknologi PETRONAS, 2018)
This project is to design and develop a multiple array vertical wind turbine which is a combination of multiple vertical axis wind turbine on a single tower. The wind turbine is design to operate under Malaysia’s wind condition and become more efficient in term of its function as a power generator. The design research begin with the study about the type of wind turbine, characteristic of wind turbine, review on wind speed in Malaysia and current trend of small scale wind turbine. Next, the methodology of designing was made by calculating the necessary parameters of the wind turbine based on turbine and generator theory. Using the calculated parameter values, the design for turbine, stator and rotor was made. A numeric model for wind turbine was simulated based on MATLAB Simulation tool. Lastly, the result from simulation is then compared to the parameter values calculated to validate the accuracy of the wind turbine design.